IDENTIFIKASI PERBEDAAN DAN UPAYA DALAM MENDUKUNG GAYA BELAJAR ANAK PADA PERIODE GOLDEN AGE - Nur Kumalasari Suratno; Pipit Priyanti; Rini Sugiarti; Fendy Suhariadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Identifying children's learning styles during the golden age period is very important to support optimal learning development. Every child has a different learning style, such as visual, auditory, or kinesthetic, and by recognizing these learning styles, educators or parents can adjust the most effective teaching methods as an effort to improve children's learning styles in the golden age period. In this research, the author uses a qualitative method by limiting the object of discussion through problem formulation, namely: How are children's learning styles different in the golden age period and how are efforts to improve and support children's learning styles in the golden age period. The results of the discussion show that each child has a different learning style. The different learning styles include: auditory learning style, visual learning style, kinesthetic learning style, social learning style, independent learning style, emotional learning style and mixed learning style. After identifying the differences in children's styles in the golden age period, efforts that can be made to improve and support children's learning styles in the golden age are encouraging children's learning style methods, adapting teaching materials to learning styles, designing activities that accommodate various styles, evaluating and adjust the approach and create a supportive learning environment, and wisely limit children's use of technology to support their social, emotional and cognitive development.